Cytotoxic Studies on Two Meliaceae plants: Chukrasia Tabularis and Aglaia Roxburghiana - Islam, M. K.; Eti, I. Z.; Chowdhury, J. A. (Journal of Scientific Research, 2009)
The paper details a biological investigation on chukrasia tabularis and aglaia roxburghiana, species of meliaceae. The methanol crude extract of chukrasia tabularis and aglaia roxburghiana have been screened for antitumor potentials using brine shrimp lethality bioassay with ten different concentrations. An established cytotoxic agent vincristine sulphate has been used to compare the results. From the graphs the concentration of methanolic crude extract yields the value of LC50 (50% mortality) as 1.58mg/ml and 2.21mg/ml for chukrasia tabularis and aglaia roxburghiana, respectively. In the same way the concentration at which 90% mortality (LC90) occurs for the methanol extract are obtained from the graphs and the values have been found to be 141.41mg/ml and 70.70mg/ml for chukrasia tabularis and aglaia roxburghiana, respectively. Keywords: Chukrasia tabularis; Aglaia roxburghiana; Meliacea; Cytotoxicity. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i2.1645